STRATEGy Seismic neTwoRk/Array in norThwEstern arGentina: Study of the 2015 El Galpón earthquake and its aftershock sequence - Zeckra, M. (2017)
After a damaging, medium-sized earthquake (Mw 5.8; October 17, 2015) in El Galpón area in the Salta Province, we installed a local seismological network around the estimated epicenter covering also remarkable tectonic and geological orographic structures. The 2015 earthquake took place in the Andean foreland at about 17km depth. The so called Santa Bárbara System is the easternmost morphostructural region of the central Andes. As a part of the broken foreland it is bounded to the north by the Subandean Belt and the Sierras Pampeanas lying in the south; to the east joins the Chaco-Paraná basin.